Mindfulness for female outpatients with chronic primary headaches: an internet-based bibliotherapy - Vahid Tavallaei; Yaser Rezapour-Mirsaleh; Peyman Rezaiemaram; Seyed Hassan Saadat (PAGEPress Publications, 2018)
Our aim was to investigate effectiveness of mindfulness by bibliotherapy on disability, distress, perceived pain and mindfulness in women with tension headaches and migraines. Primary headaches have been of great interest to mental health researchers because of the high prevalence, as well as significant disability and distress in the affected people. Despite the promising results of in-person treatment and some limitations that such interventions may cause, patients may be encountered with problems when using health care services. The present study is a quasi-experimental randomized design with pre-test, post-test, and control group. The study population consisted of 1396 women with migraine headache referring to headache clinic of Baqiyatallah Hospital in Tehran. Of these, 30 patients (including tboh experimental and control group) were selected by objective sampling method and were randomly assigned to the two groups. The experimental group, in addition to medical treatment as usual, was treated for a period of 8 sessions by Mindfulness-based Stress Reduction Internet-based Bibliotherapy, but the control group used only the medical treatment. The sample had no attritions. Data were collected by the four scales of (DASS-21), Migraine Disability Assessment Test (MIDAS), McGill's Short Form Questionnaire (MPQ-SF), and Mindfulness Inventory (MAAS). We used covariance analysis to analyze the findings in the measured scales. MBSR-IBB treatment had no significant effect on pain sensory dimension (P<0.44), despite improvement of mindfulness (P<0.0001). In contrast, the greatest effect was on the level of disability (P<0.0001). We observed also a significant improvement in distress (P<0.0001). In conclusion, in spite of the presence of headaches, the mindfulness improved the quality of life and reduced the level of mental distress. In addition, using the Internet-based bibliotherapy method, these services can be used with easier access, lower cost, and more flexibility.